Review Artikel: Pengembangan Sediaan Padat dengan Penyalutan Zat Aktif dari Bahan Alam - Dilla Chairunnisa, Asa; Purnama Sari Siahaan, Desy; Mega Utami, Wahyuni; Reza Pahlevi, Muhamad; Sutoro, Meylani (LP4M STIKes Karsa Husada Garut, 2025)
Introduction: Introduction: This study aims to examine natural materials that can be formulated into coated solid preparations in the pharmaceutical world. Coated solid preparations have various benefits, including increasing the stability of active substances, protecting materials from the external environment such as light, heat, oxygen, and covering unpleasant tastes. Methods: This study was conducted through a literature search using the Google Scholar, ScienceDirect, and ResearchGate databases, with inclusion criteria in the form of research journals on natural materials made into coated solid preparations. Results: The study shows that natural materials such as plant extracts, probiotics, aromatic resins, fish oil, and oleoresins can be formulated into several forms of coated solid preparations, including film-coated tablets, film-coated tablets, encapsulates, microcapsules, and microparticles (pellets). Commonly used coating materials include HPMC (Hydroxypropyl methyl cellulose), PVA (Polyvinyl alcohol), opadry AMB, maltodextrin, and kollicoat protect. Some examples of natural ingredients that have been applied are pomegranate peel extract as an antimalarial, gambir leaf extract as an antidyslipidemia, and probiotics from fermented snake fruit. Conclusion: the formulation of solid preparations coated with natural ingredients provides significant benefits in increasing the effectiveness and stability of pharmaceutical preparations, while utilizing natural ingredients that have biological activity. This study is expected to be a reference in the development of pharmaceutical preparations based on natural ingredients.